Elastic and durable multi‐cation‐crosslinked anion exchange membrane based on poly(styrene‐b‐(ethylene‐co‐butylene)‐b‐styrene). Issue 16 (31st July 2020) - Li, Ziming; Li, Conghui; Long, Chuan; Sang, Jing; Tian, Lin; Wang, Fanghui; Wang, Zhihua; Zhu, Hong
Abstract: Anion exchange membranes (AEMs), as the core component of the new generation anion exchange membrane fuel cells (AEMFCs), directly determine the performance and the lifetime of this energy conversion device. Here, AEMs with pendant multiple quaternary ammonium anchored onto the poly(styrene‐ b ‐(ethylene‐ co ‐butylene)‐ b ‐styrene) (SEBS) backbone are synthesized. The comb‐shaped copolymer SEBS‐C16 is synthesized with N, N ‐dimethyl‐1‐hexadecylamine and chloromethylated SEBS to improve solubility, then the multi‐cation crosslinker is prepared and grafted on the above backbone to fabricate a series of flexible multi‐cation crosslinked SEBS‐based AEMs (SEBS‐C16‐xC4, where x% is the ratio of the crosslinker to polystyrene block) with practical properties. The obtained SEBS‐C16‐20C4 membrane exhibits a microphase separated morphology with an interdomain spacing of 18.87 nm. Benefited from the ion channels, SEBS‐C16‐20C4 shows high conductivity of 77.78 mS/cm at 80°C. Additionally, the prepared SEBS‐C16‐20C4 membrane with ion exchange capacity of 2.35 mmol/g also exhibits enhanced alkaline stability (5.87% hydroxide conductivity decrease in 2 M NaOH solution at 80°C after 1, 700 hr) and improved mechanical properties, compared with the non‐crosslinked SEBS‐C16 sample. Furthermore, AEMFC single cell performance is evaluated with the SEBS‐C16‐20C4 membrane, and a maximum power density of 182 mW/cm 2 is achieved at 80°C under H2 /O2 conditions. Abstract : Poly(styrene‐ b ‐(ethylene‐co‐butylene)‐ b ‐styrene) with flexible long alkyl chains is synthesized to enhance the solubility. Then the multi‐cation crosslinker is anchored onto the comb‐shaped copolymer to prepare the anion exchange membranes with a good performance. Distinct microphase separated morphology is constructed for the efficient transformation of ions. Dimensional and chemical stabilities are both improved due to the crosslinking architecture. Single fuel cell performance test is also investigated for practical issues.